MENEROPONG NILAI-NILAI MORAL DALAM UPACARA REBA KAMPUNG TUREKISA, KABUPATEN NGADA - Fladimir Sie; Siprianus Soleman Senda (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2025)
This paper discusses local cultural products in Ngada Regency. The material object is the Reba Ceremony. The Reba Ceremony is an integral part of Ngada's culture, containing important moral and social values in daily life. As an annual event, Reba is not only a harvest celebration but also serves as a means of conveying moral messages and life teachings. This study aims to explore the moral values embedded in the Reba traditional ceremony in Turekisa Village, Ngada Regency. Using a qualitative research method and a descriptive approach, data were collected through in-depth interviews, participatory observation, and literature studies. The findings indicate that the Reba ceremony contains profound moral messages, including teachings about hard work, mutual cooperation, respect for nature, and the importance of harmonious social relationships. This ceremony also plays a role in resolving social conflicts, strengthening community bonds, and preserving cultural values for the younger generation. The moral values in Reba help shape the social, political, and religious life of the Ngada people, making it an important tool for cultural education.